The origins of democratic Zionism - Kaplan, Gregory B. 1966-; Kaplan, Gregory B. 1966- (London New York Routledge Taylor & Francis Group, 2019)
List of abbreviations -- Preface -- Acknowledgments -- Introduction: From Democracy to Democratic Zionism -- Flawed Democracy, the Aristotelian Agricultural Democracy and the Hebrew Republic -- The Medieval Divine-Right Monarchy, an Anti-Hebrew Republic -- The Divine-Right Spanish Monarchy and the Conversos -- The Hebrew Republic as an Alternative to Habsburg Rule and the Emergence of Morteira, Barrios and Spinoza -- The Hebrew Republic and Democratic Zionism in the Writings of Morteira -- Morteira, Hobbes and the Democratic Zionism of Spinoza and Barrios -- Democratic Zionism and Twenty-First Century Zionism -- Appendix: Treatise on the Truth of the Law of Moses, Chapters One, Two, Ten and Eleven (Translation into English by Gregory B. Kaplan) -- Index.
"This book is the first to link the modern appreciation for democratic freedom directly to Jewish political thought in seventeenth-century Amsterdam. The modern appreciation for democratic values is often assumed to have its roots in Classical thought. However, democracy has taken various forms in its progression to the governance many countries now employ. Working in dialog with Protestants, Jewish thinkers voiced the first Modern appeal for the reestablishment of a Jewish polity in the Holy Land. This appeal was grounded in a vision of a Jewish state governed by individual liberty and popular consent, which could be defined as a democratic Zionism. The book focuses on influential rabbi Saul Levi Morteira, as well as two of the most renowned members of his congregation, Baruch Spinoza and Miguel de Barrios. Unlike contemporary Catholic and Protestant thinkers, these three intellectuals found democratic values in an Old Testament polity that came to be revered as the Hebrew Republic. The book explores the trajectory by which this democratization of the Hebrew Republic evolved in the writings of Morteira as an alternative to divine-right rule. It then shows that, in spite of their divergent views toward practicing Judaism, Spinoza and Barrios disseminated Morteira's democratic ideas and promoted the Hebrew Republic as a model polity for a post-medieval political order. This book will be of great use to scholars of Judaism and Jewish philosophy in the modern era, medieval and early modern Spanish literature, as well as religious, political and intellectual history" --
Includes bibliographical references and index
Keywords: Mortera, Saul Levi -- 1596?-1660; Spinoza, Benedictus de -- 1632-1677; Barrios, Miguel de -- 1635-1701; Zionism -- History; Democracy -- Religious aspects -- Judaism; Judaism and state